The Effect of Health Education about Low Purine Diet through Video Media on the Level of Knowledge of Gout Patients - Ningsih, Tri Hadi; Yuniartika, Wachidah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Gout is a disease caused by the accumulation of monosodium grate crystals in the human body. The cause of the high incidence of gout is a lack of knowledge about preventing gout, so efforts can be made with Health Education to increase understanding. This research aims to determine the effect of health education about a low-purine diet delivered through video media on the level of knowledge among gout sufferers. This quantitative research employs a quasi-experimental study design, specifically a